2012
DOI: 10.1177/159101991201800208
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Post-Traumatic Carotid-Cavernous Fistulas with the Willis Covered Stent

Abstract: We describe our preliminary experience on the feasibility of using the Willis covered stent in patients with carotid-cavernous fistulas (CCFs). Eleven consecutive patients with post-traumatic CCFs referred for treatment with Willis covered stents were enrolled into this prospective study, and were subsequently followed-up at our hospital. Data on technical success, initial and final angiographic results, mortality, morbidity and final clinical outcome, was collected, with follow-up p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 16 publications
1
12
0
Order By: Relevance
“…Covered stents can be used in some conditions in which detachable balloons and coils cannot be utilized. The reported success rate to date of detachable balloon, flow diverter and covered stent for occlusion of TCCF as primary treatment modality was 55–98% [ 8 , 14 , 20 ], 71% [ 42 ], and 75–100% [ 12 , 26 , 41 ], respectively and our results were similar with previous reports. Moreover, it has advantages in the concept of one-step and time-saving treatment in emergency situations.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Covered stents can be used in some conditions in which detachable balloons and coils cannot be utilized. The reported success rate to date of detachable balloon, flow diverter and covered stent for occlusion of TCCF as primary treatment modality was 55–98% [ 8 , 14 , 20 ], 71% [ 42 ], and 75–100% [ 12 , 26 , 41 ], respectively and our results were similar with previous reports. Moreover, it has advantages in the concept of one-step and time-saving treatment in emergency situations.…”
Section: Discussionsupporting
confidence: 90%
“…A recent study used a covered stent in DCCF and reported the outcomes [ 2 , 5 , 12 , 16 , 25 , 26 , 38 , 40 , 41 ]. Covered stents can be used in some conditions in which detachable balloons and coils cannot be utilized.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a new kind of covered stent specifically designed for intracranial use has reduced on the problem. The stent is reported to be more flexible and to achieve good preliminary results in DCCF treatment 18) . Further progress can be anticipated as technology of the covered stents and their delivery systems continue to evolve.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has not been widely applied, because it is sometimes difficult to position it in place. [ 17 19 ] Gel or coil embolization is the most effective treatment for patients with type V (Fig. 4 B).…”
Section: Discussionmentioning
confidence: 99%